Performance Analysis of Asynchronous Carrier InterferometryMC-CDMA Uplink with Interference Cancellation Techniques - Thippavajjula, V.; Natarajan, Bala (Institute of Electrical and Electronics Engineers, 2005)
In this paper, we analyze the uplink performance of an asynchronous carrier interferometry/MC-CDMA, with nonlinear parallel and serial interference cancellation techniques. Specifically, we employ the new variant of parallel interference cancellation known as block-PIC and demonstrate significant performance (10 dB) improvement relative to conventional PIC. We also study the effect of order of cancelling in serial interference cancellation by comparing the performance of the conventional fixed ordering scheme with dynamic ordering. We show that dynamic ordering provides a gain of 8 dB relative to fixed ordering.
Keywords: Code division multiple access; Fading channels; Interference suppression; Interferometry; Radion links; Asynchronous CI